Fla. Jail Achieves Cost Savings With ACA Online Training. - Geiman, Diane (Corrections Today)
The article features the Saint Lucie County Jail in Fort Pierce, Florida which is using online training for its staff. Topics covered include the accreditations and compliance standards achieved by the jail, the contract with the Corrections Online Training Collaborative (COTC), and the costs-effectiveness and benefits of the online training program. Also mentioned are ways to enhance their current online training program.